Cascading Gamification Learning Model for Awareness Program: A Case Study of Online Safety Awareness Among Children - Tan, Ping Ping; Jacey Lynn, Minoi; Lim, Phei Chin; Eaqerzilla, Phang; Jaya Laxshmi, Meenatchisundaram (2025)
This paper investigates innovative strategies for nurturing global citizenship skills among students with special needs in Oman. Recognizing the critical importance of equipping these students with essential 21st-century competencies such as critical thinking, creativity, communication, and collaboration, the study delves into practical methods that ensure their active participation in a rapidly evolving world. By integrating Universal Design for Learning (UDL), assistive technologies, and project-based learning (PBL), educators can create inclusive environments that cater to the diverse needs of students. These methods not only address individual learning barriers but also promote engagement and empowerment, enabling students to tackle real-world challenges collaboratively. Aligned with Oman’s Vision 2040, this framework underscores the importance of inclusive education as a national priority. The paper examines successful case studies, such as collaborative environmental projects and cultural preservation through technology, showcasing how these approaches bridge gaps and foster global citizenship skills. Challenges like resource limitations and cultural stigmas are also addressed, with proposed solutions emphasizing policy advocacy, professional development, and community engagement. Ultimately, this study illustrates how inclusive practices can transform special needs education in Oman, equipping students with the tools to contribute meaningfully to their communities and the global stage.